Punching the air - Zoboi, Ibi Aanu; Salaam, Yusef, 1974- (Balzer & Bray, an imprint of HarperCollins Publishers, 2020)
From award-winning, bestselling author Ibi Zoboi and prison reform activist Yusef Salaam of the Exonerated Five comes a powerful YA novel in verse about a boy who is wrongfully incarcerated. The story that I thought was my life didn't start on the day I was born. Amal Shahid has always been an artist and a poet. But even in a diverse art school, he's seen as disruptive and unmotivated by a biased system. Then one fateful night, an altercation in a gentrifying neighborhood escalates into tragedy. "Boys just being boys" turns out to be true only when those boys are white. The story that I think will be my life starts today. Suddenly, at just sixteen years old, Amal's bright future is upended: he is convicted of a crime he didn't commit and sent to prison. Despair and rage almost sink him until he turns to the refuge of his words, his art. This never should have been his story. But can he change it' With spellbinding lyricism, award-winning author Ibi Zoboi and prison reform activist Yusef Salaam tell a moving and deeply profound story about how one boy is able to maintain his humanity and fight for the truth, in a system designed to strip him of both.